(x+3)(x+3)=8x

Simple and best practice solution for (x+3)(x+3)=8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+3)(x+3)=8x equation:


Simplifying
(x + 3)(x + 3) = 8x

Reorder the terms:
(3 + x)(x + 3) = 8x

Reorder the terms:
(3 + x)(3 + x) = 8x

Multiply (3 + x) * (3 + x)
(3(3 + x) + x(3 + x)) = 8x
((3 * 3 + x * 3) + x(3 + x)) = 8x
((9 + 3x) + x(3 + x)) = 8x
(9 + 3x + (3 * x + x * x)) = 8x
(9 + 3x + (3x + x2)) = 8x

Combine like terms: 3x + 3x = 6x
(9 + 6x + x2) = 8x

Solving
9 + 6x + x2 = 8x

Solving for variable 'x'.

Reorder the terms:
9 + 6x + -8x + x2 = 8x + -8x

Combine like terms: 6x + -8x = -2x
9 + -2x + x2 = 8x + -8x

Combine like terms: 8x + -8x = 0
9 + -2x + x2 = 0

Begin completing the square.

Move the constant term to the right:

Add '-9' to each side of the equation.
9 + -2x + -9 + x2 = 0 + -9

Reorder the terms:
9 + -9 + -2x + x2 = 0 + -9

Combine like terms: 9 + -9 = 0
0 + -2x + x2 = 0 + -9
-2x + x2 = 0 + -9

Combine like terms: 0 + -9 = -9
-2x + x2 = -9

The x term is -2x.  Take half its coefficient (-1).
Square it (1) and add it to both sides.

Add '1' to each side of the equation.
-2x + 1 + x2 = -9 + 1

Reorder the terms:
1 + -2x + x2 = -9 + 1

Combine like terms: -9 + 1 = -8
1 + -2x + x2 = -8

Factor a perfect square on the left side:
(x + -1)(x + -1) = -8

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| 20-16y=-19-19y | | p+4b=120 | | 2x+x+(x+2)=30 | | -208=-21x+212 | | -11-22=33 | | 7(4x-5)-4(6x-5)=-91 | | -2j-20=8j | | 8z=122 | | 65+90+5x=180 | | -3-y-X=0 | | 2x-8=-8x-24 | | 2(4-9w)= | | 57+51+9x=180 | | 6(-2y-16)-2y=-12 | | 6p+b=144 | | -18s+10=-17s | | (X+18)=(x+10) | | 18x-12=17x-2 | | 0=-x+5y | | 3(2z)=-3 | | -690=10(-7x+22) | | 5x-9x+3=17 | | 8x-4(-3+2)=-12 | | 2m+6n-9(5m-4n)= | | (2x-8)(2x-8)=44 | | 12x+15y=90 | | 100-66=31y-35y | | 10=-x+2y | | 2x-18=9x+6 | | 7.57x+22.71=45.42 | | 5+3t-3=8t+14-3t | | (X+14)=(x-20) |

Equations solver categories